1987
DOI: 10.1007/bf02370645
|View full text |Cite
|
Sign up to set email alerts
|

Fungicide seed treatments increase growth of perennial ryegrass

Abstract: Field, laboratory and glasshouse experiments were carried out to measure effects of seed treatments with captan or thiram on growth of perennial ryegrass (Lolium perenne L.). Field-sown captan-or thiram-treated seed gave twice as many seedlings as untreated seed. Spaced plants growing from fungicide-treated seed produced almost 6 times more dry matter 16 weeks after sowing than those from untreated seed. This effect, though diminishing with time, was still apparent more than a year after sowing. Fungicides in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…These results parallel those obtained from ryegrasses (Falloon, 1980;1987), and reinforce the suggestion of CuIIeton and McCarthy (1983) that prairie grass seedlings growing in cool soils may be more susceptible to soil-borne pathogens than those growing in warmer conditions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results parallel those obtained from ryegrasses (Falloon, 1980;1987), and reinforce the suggestion of CuIIeton and McCarthy (1983) that prairie grass seedlings growing in cool soils may be more susceptible to soil-borne pathogens than those growing in warmer conditions.…”
Section: Discussionsupporting
confidence: 90%
“…This study has demonstrated that fungicide seed treatment with thiram can increase numbers of seedlings that establish from prairie grass sowings in autumn. These results parallel those obtained from ryegrasses (Falloon, 1980;1987), and reinforce the suggestion of CuIIeton and McCarthy (1983) that prairie grass seedlings growing in cool soils may be more susceptible to soil-borne pathogens than those growing in warmer conditions. The beneficial effects of thiram seed treatment on prairie grass seedling establishment gave only short-term advantages in herbage production.…”
Section: Discussionsupporting
confidence: 88%
“…However, despite surface sterilization with bleach and the use of sterile equipment, fungal growth was a significant problem in our experiment, particularly for seeds from WFD. To control the spread of fungus, we treated Petri dishes with a dilute solution of captan fungicide (3.5 g/L), a tissue culture and seed sterilization treatment (Falloon, 1987; Payamnour et al., 2014).…”
Section: Methodsmentioning
confidence: 99%